Proteç\~ao efetiva no Brasil: 2000 a 2015 - Carolina Bloch; Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper calculates effective tariffs by industrial sector for Brazil from 2000 to 2015. Effective tariff differs from nominal tariff in that it takes into consideration the protection given to industrial inputs so that a sector whose products are protected by high tariffs may also be burdened by high tariffs on its inputs, leading to a lower effective tariff. Two series are calculated: 2000 to 2009 and 2010 to 2015. The reason for this is that the National Accounts changed their classification of economic sectors in 2010. Results indicate that: i) effective rates of protection are highly varied in Brazil, according to sector; ii) effective rates of protection have fallen slightly in the 15 years from 2000 to 2015; and iii) some sectors have seen their rates of protection vary considerably over this fifteen-year period, but in most sectors the ERP did not vary much.
Keywords: F13; 330; trade policy; effective rates of protection; nominal rates of protection